PEMBERDAYAAN BERBASIS PESANTREN: DARI ANTI-BULLYING HINGGA PEMANFAATAN SAMPAH UNTUK LINGKUNGAN SEHAT - Susanti, Ani; Muhyidin, Ayi; Layyin, Fela; Inan, Siti Maryam; Auliawan, Budi; Hasanah, Ulfa; Ruslan, Mochamad; Prihatiningsih, Rika; Azarine, Rahma Ardina; Tsabita, Alya Shosho; Mentari, Mentari (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Islamic boarding schools are Islamic educational institutions that not only function as places of religious learning but also as centers for character building, spirituality, and social development of students. As a community that is generally inhabited by hundreds or even thousands of students, Islamic boarding schools face various challenges in environmental management and student welfare. The community service program by students of ITB Ahmad Dahlan Jakarta's Community Service Program (KKN) has a strategic role to play in helping Islamic boarding schools overcome these problems. Through the KKN program, students can collaborate with the boarding school to provide a safe and healthy space for students, provide education on the importance of waste sorting and how to manage it, and utilize existing land to grow vegetables. The way KKN is carried out consists of conducting surveys, planning work program activities that are in accordance with the conditions and problems that exist in the boarding school. Student work program activities were welcomed by the MIBS Kebumen boarding school. This is indicated by the involvement of all MIBS students in all work programs implemented. Forms of activities that involve all students are Launching a Safe and Healthy Santri Room (RASSA), Anti Bullying seminars, seminars on the management and utilization of organic and inorganic waste and planting vegetables by utilizing inorganic waste which is carried out in the MIBS Kebumen Islamic boarding school environment. Real Work Lecture (KKN) students are expected to provide benefits for students and MIBS Kebumen boarding school, especially aiming to create significant changes in mental health and physical health for students and give a good impression for the boarding school.